Potensi Antimikroba Fraksi Etil Asetat Daun Mangkokan (Nothopanax scutellarius (Brum.f.) Fosberg) Terhadap Berbagai Mikroba Patogen - Goldha Faroliu; Annisa Fitri Angraini; Atyka Putri Wisni (JURNAL FARMASI DAN MAKANAN, 2023)
Mangkokan leaves (Nothopanax scutellarius (Brum.f.) Fosberg) is an ornamental plant that usually grows in home gardens, relatively popular and is used as an alternative medicine such as improving the digestive system, preventing hair loss, treating wounds, anti-inflammation, improving blood flow, preventing the appearance of symptoms of anemia and antioxidants. This study aims to determine the inhibitory power of extracts and ethyl acetate fractions towards Salmonella gastroenterites, Lactobacillus rhamnosus, Eschericia coli, Bacillus subtilis, and Candida albicans. The ethanol extract of mangkokan leaves contains alkaloids, saponins, phenolics, steroids and terpenoids, and the ethyl acetate fraction of mangkokan leaves shows that it contains phenolic, steroids and terpenoids. The ethanol extract and ethyl acetate fraction of mangkokan leaves has the ability to inhibit the growth of Salmonella gastroenterite, Lactobacillus rhamnosus, E.coli, B.subtilis, and C.albicans, with moderate categories of antibacterial activity and weak category for antifungal activity. It can be concluded that mangkokan leaf extracts and fractions have the potential to be antimicrobial.